Asymmetric Michael addition reactions of nitroalkanes to 2-furanones catalyzed by bifunctional thiourea catalysts1. Issue 19 (21st May 2015) - Bai, Zhushuang; Ji, Ling; Ge, Zemei; Wang, Xin; Li, Runtao
<x xml:space="preserve">Abstract</x> The first bifunctional thiourea catalyzed asymmetric Michael addition reactions of nitroalkanes to 2-furanones are described.